2020
DOI: 10.30574/wjbphs.2020.3.1.0037
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin and C-reactive protein level among smoker and non-smoker individuals of Kathmandu valley, Nepal

Abstract: Cigarette smoking contribute to the development or progression of numerous chronic and age related disease processes. One major risk factor for morbidity and mortality among smokers is cardiovascular disease and lungs cancer. Hematological abnormalities have been associated with coronary heart disease and other oxidative damage at the tissue level increasing in age is significantly associated with higher hemoglobin concentration and C-reactive protein reactivity. The aim of the study was to find out the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Further, in multivariable linear regression analysis in Table 3 , after adjusting for age, gender, BMI, physical activity, and HEI, we found that current and heavy smokers and smoking cigarettes over 15 years’ groups had a maximum positive significant correlation with HCT, HGB, MCV, MCH, and MCHC. Tobacco generates more than five thousand chemical compounds, including gases and particulates like nicotine, nitrosamine, formaldehyde, and carbon monoxide, and hydrogen cyanide [ 3 ]. In alveolar capillaries, carbon monoxide(CO) with a binding ability of 200–250 times greater than oxygen can bind firmly to the HGB, forming carboxyhemoglobin and leading to hypoxia in tissues subsequently leading to high values of HGB and RBC count in smokers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, in multivariable linear regression analysis in Table 3 , after adjusting for age, gender, BMI, physical activity, and HEI, we found that current and heavy smokers and smoking cigarettes over 15 years’ groups had a maximum positive significant correlation with HCT, HGB, MCV, MCH, and MCHC. Tobacco generates more than five thousand chemical compounds, including gases and particulates like nicotine, nitrosamine, formaldehyde, and carbon monoxide, and hydrogen cyanide [ 3 ]. In alveolar capillaries, carbon monoxide(CO) with a binding ability of 200–250 times greater than oxygen can bind firmly to the HGB, forming carboxyhemoglobin and leading to hypoxia in tissues subsequently leading to high values of HGB and RBC count in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is the most preventable account of death globally [ 2 ]. Cigarette smoke ingredients, including carbon monoxide, hydrogen cyanide, benzene, nitrosamines, and nicotine, are toxic and, cause damage to the body in several ways [ 3 ]. Smokers have a higher chance of developing cardiovascular disease, cancers, and pulmonary diseases [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation